Blood pressure, antihypertensive drugs, and incident frailty: The Multidomain Alzheimer Preventive Trial (MAPT). (August 2022) - Rouch, Laure; Rolland, Yves; Hanon, Olivier; Vidal, Jean-Sébastien; Cestac, Philippe; Sallerin, Brigitte; Andrieu, Sandrine; Vellas, Bruno; Barreto, Philipe De Souto; ,
Highlights: Low blood pressure was associated with a 40% increase in the risk of frailty. Participants with low blood pressure and those on two or more antihypertensive drugs were at the greatest risk of frailty. Low blood pressure could be a new marker for identifying older adults at higher risk of frailty. Abstract: Objectives: To examine the association of (1) high and low blood pressure (BP) and (2) antihypertensive (AH) drug use with incident frailty. Study design: We conducted a secondary analysis of data from the Multidomain Alzheimer Preventive Trial (MAPT), in which 1394 non-frail community-dwelling participants aged ≥70 years were followed up for 5 years. BP was measured once at baseline in a lying position using a validated electronic device. High BP was defined as systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg, and low BP as systolic BP ≤ 110 mm Hg and/or diastolic BP ≤ 70 mm Hg. AH drugs were assessed at baseline and classified according to the Anatomical Therapeutic Chemical (ATC) code. Main outcome measures: Incident frailty over the 5 years was assessed using the Fried phenotype. Cox proportional hazards models were used for the analyses. Results: Low BP was associated with a greater risk of frailty (HR = 1.43, 95% CI [1.07–1.92], p = 0.02) after adjustment for age, sex, education, AH drug use, BMI, diabetes, ischemic heart disease, congestive heart failure, AF, stroke, MAPT randomization group, sit-to-stand chair test and pre-frailty. Participants with low BP and those on two or more AH drugs were at the greatest risk of frailty. Neither high BP (HR = 0.84, 95% CI [0.63–1.22], p = 0.24) nor AH drug use (HR = 1.21, 95% CI [0.89–1.64], p = 0.22) was independently associated with incident frailty. Conclusions: Low BP could be used as a new marker for identifying older adults at higher risk of frailty. Clinicaltrials.gov registration number: NCT00672685 .